Exploring Pancasila Education Learning with Canva Based on Deep Learning for Student Independence - Pasha, Dwi Ayu Dian; Triyanto, Triyanto; Chumdari, Chumdari (Social, Humanities, and Educational Studies (SHES): Conference Series, 2026)
This study aimed to explore the implementation of Pancasila Education learning using Canva-based deep learning media to foster independence among second grade elementary school students. The research employed a qualitative descriptive case study approach, with data collected through classroom observations, semi-structured interviews, and documentation. The findings showed that the integration of Canva media, encouraged students to engage more actively in classroom activities, with 81.5% of students showing positive responses. The media supported students in completing self-directed tasks and enhanced their sense of responsibility and self-evaluation. Overall, the use of Canva proved to be effective in promoting student independence in elementary education.